No Cutting Corners: The Effect of Parental Involvement on Youth Basketball Players in Israel - Lev, Assaf; Bichman, Adi; Moyal, Avi; Brenner, Shmulik; Fass, Nir; Been, Ella (Frontiers in Psychology, 2020)
This paper explores the nature of parental involvement in youth basketball in Israel with regards to parenting style and in the context of dilemmas and ethical issues. It is well established that parental involvement in their child’s sporting activity has vast implications on the child's motivation and enjoyment. With reference to Israeli society, only a few studies have focused on this subject. In order to address this lacuna, we used two questionnaires, given to 173 youth basketball players (child questionnaire) and their parents (parent questionnaire). Key findings illustrate three main themes. First, a higher level of satisfaction and contentment among basketball players whose parents demonstrated greater involvement; second, that parental emotional involvement is the most important variable for young athletes’ satisfaction; and finally, differences in gender roles reveal that fathers are more involved with logistics while mothers are more dominant in emotional involvement. Moreover, the findings demonstrate that parents should mainly place emphasis on emotional involvement. However, we suggest that parents not bypass logistical care as this may create opportunities for greater emotional support and therefore greater child satisfaction.